2014
DOI: 10.3844/ajavsp.2014.303.314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyme, Clove and Cinnamon Essential Oils on <i>Candida Albicans</i> and Moulds Isolated from Different Sources

Abstract: In this study, mycological examination were conducted on different samples from human, animals and poultry in El-Fayoum and Beni-Suef governorates, Egypt in the period from January to June 2013. The antifungal activities of thyme, clove and cinnamon oils against the recovered fungal isolates were tested using agar dilution method. A total of 209 samples were collected (including vaginal swabs from 18 women, 82 cows and 9 buffaloes beside 100 swabs from broiler chickens; 20 crops and 80 proventriculus). Eighty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 46 publications
(60 reference statements)
4
18
2
Order By: Relevance
“…The essential oils contain a variety of volatile molecules including terpenes, terpenoids, aldehydes, ketones, lactones and phenolic compounds which have antifungal consequences (Bakkali et al, 2008 andAkthar et al, 2014). Several studies have been emitted to clarify the effect of essential oils and their main compounds on different Candida species (Benlafya et al, 2014;Radwan et al, 2014 andKaro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils contain a variety of volatile molecules including terpenes, terpenoids, aldehydes, ketones, lactones and phenolic compounds which have antifungal consequences (Bakkali et al, 2008 andAkthar et al, 2014). Several studies have been emitted to clarify the effect of essential oils and their main compounds on different Candida species (Benlafya et al, 2014;Radwan et al, 2014 andKaro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial activities of essential oils extracted from plants have been reported by: Nzeako et al, 2006, showing antimicrobial activities of clove and thyme extracts; Chee and Lee (2007) showed antifungal activity of clove essential oil and its volatile vapour against Dermatophytic Fungi; Radwan et al (2014) showed in a study regarding antifungal activity of thyme, clove and cinnamon essential oils on Candida albicans and moulds isolated from different sources that thyme oil completely inhibited the growth of different fungal isolates at concentrations of 0.25, 0.5 and 1%; Surdu et al (2014) studied improvement of the resistance to Candida albicans and Trichophyton interdigitale of some woven fabrics based on cotton.…”
Section: Introductionmentioning
confidence: 99%
“…Studies prove conclusively that certain essential oils work as powerful antifungals [3][4][5]. Some essential oils have the ability to kill parasites and fungal infections, which is why they are so popular for use in fighting toenail fungus, ringworm and athlete's toenail infection.…”
Section: Introductionmentioning
confidence: 99%